MARKETING CONCEPT TO IMPROVE BUSINESS ASSOCIATIONS’ ACTIVITY EFFECTIVENESS - L. Paschuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The major problems and perspectives of Ukrainian business associations were defined, definition of business association was developed, key stakeholders of business association were subdivided, marketing mix components of non-profit organisation were identified.